Évaluation de l'adsorption de deux bactéries fécales par l'horizon argilo-sableux et l'horizon quartzo-feldspathique d'un sol ferralitique au Cameroun (Afrique Centrale). Issue 5 (1st September 2003) - Nola, Moïse; Njiné, Thomas; Servais, Pierre; Messouli, Mohamed; Boutin, Claude; Menbohan, Samuel Foto; Kemka, Norbert; Zébazé Togouet, Serge H
Abstract : A laboratory study has been carried out to assess the retention capacity of Streptococcus faecalis and Escherichia coli by two ferralitic soil horizons: the upper soil horizon (H A ), linked to the soil surface and of sandy-clayed texture, and the deeper soil horizon (H Q ), related to the groundwater table and of quartzo-feldspathic texture. Bacterial sorption on soil particles swiftly took place during the first 30 min that followed mixture of bacteria to the aqueous medium containing soil. The number of adsorbed bacteria sometimes undergoes temporal fluctuations. From Freundlich isotherms used, the linear coefficient of H A led from 0.5139 to 0.8932 and that of H Q varied from 0.0634 to 0.5849. It was lower when E. coli and S. faecalis were present at the same time, and greater when S. faecalis only was present. The adsorption coefficient of H A varied from 174 to 49.55 x 10 6 bacteria/mg of soil, and that of H Q varied from 4026 to 13.74 x 10 4 bacteria/mg of soil. A low adsorption coefficient of H A is seen when S. faecalis only is present, and that of H Q is also low when E. coli only is present. In the presence of the two bacterial species, adsorption coefficients of the two soil horizons rises. Key words : Escherichia coli, Streptococcus faecalis, adsorption, sandy-clayed soil, quartzo-feldspathic soil.[Journal translation]